2022
DOI: 10.1002/term.3338
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma in the treatment of scars, to suggest or not to suggest? A systematic review and meta‐analysis

Abstract: Despite the rising trend for applying platelet‐rich plasma (PRP) in the management of various types of scars, there is no convincing evidence supporting its use. This motivated us to review the randomized clinical trials that examine the effectiveness and safety of PRP, alone or in combination with other methods, for the management of atrophic or hypertrophic/keloidal scars. The Web of Science, Scopus, Google Scholar, and Cochrane Library databases were systematically searched until September 1st, 2020. Thirte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 54 publications
1
11
0
1
Order By: Relevance
“…10,26 A meta-analysis conducted by Ebrahimi et al assessed the efficacy of PRP, either alone or in combination with other modalities, for managing atrophic or hypertrophic/keloidal scars. 27 Similarly, Tasmania et al reported the effectiveness of PRP in reducing the wound area of diabetic foot ulcers compared with conventional treatment alone, 28 which aligns with our findings. However, other studies failed to identify significant differences or positive effects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…10,26 A meta-analysis conducted by Ebrahimi et al assessed the efficacy of PRP, either alone or in combination with other modalities, for managing atrophic or hypertrophic/keloidal scars. 27 Similarly, Tasmania et al reported the effectiveness of PRP in reducing the wound area of diabetic foot ulcers compared with conventional treatment alone, 28 which aligns with our findings. However, other studies failed to identify significant differences or positive effects.…”
Section: Discussionsupporting
confidence: 90%
“…By delivering PRP or PRF to wounds, the abundance of growth factors can be utilized to expedite healing and promote larger healing areas in various types of skin wounds 10,26 . A meta‐analysis conducted by Ebrahimi et al assessed the efficacy of PRP, either alone or in combination with other modalities, for managing atrophic or hypertrophic/keloidal scars 27 . Similarly, Tasmania et al reported the effectiveness of PRP in reducing the wound area of diabetic foot ulcers compared with conventional treatment alone, 28 which aligns with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption has been supported by Ebrahimi et al which showed that marked and excellent response rate to be similar among both groups (65% vs. 66%). The study also showed that the combined use of PRP with microneedling or laser therapy generally shows better clinical improvement than any of these methods alone 41 . On the other hand, Ibrahim et al in a clinical trial showed a comparable clinical improvement and side effect profile with the combined use of PRP and microneedling versus microneedling alone in treating acne scars 42 …”
Section: Discussionmentioning
confidence: 93%
“…The study also showed that the combined use of PRP with microneedling or laser therapy generally shows better clinical improvement than any of these methods alone. 41 On the other hand, Ibrahim et al in a clinical trial showed a comparable clinical improvement and side effect profile with the combined use of PRP and microneedling versus microneedling alone in treating acne scars. 42 FCO 2 laser shows substantial clinical efficacy in the management of atrophic acne scars, the post-inflammatory hyperpigmentation (PIH) stands as a considerable obstacle, especially in dark skin types.…”
Section: Duration Of Edemamentioning
confidence: 98%
“…Additionally, platelets can also release numerous anti-inflammatory cytokines such as interleukin-1 receptor antagonist (IL-1ra), soluble tumor necrosis factor (TNF) receptor (sTNF-R) I, interleukin (IL)-4, IL-10, IL-13, and interferon γ [ 73 ]. PRP has been used as an autologous injection for various medical conditions to promote healing and tissue regeneration/rejuvenation [ 73 , 74 , 75 , 76 , 77 , 78 ]. Additionally, PRP has also been used widely in alopecia treatment due to its ability to induce cell proliferation, supporting HF growth, and extending anagen [ 72 , 79 , 80 , 81 , 82 ].…”
Section: Cia Treatmentmentioning
confidence: 99%